2005
DOI: 10.1590/s0102-86502005000200007
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do Tenoxicam sobre a cicatrização da parede abdominal: estudo experimental em ratos

Abstract: RESUMOObjetivo: Analisar os efeitos do tenoxicam, um antiinflamatório não hormonal, na cicatrização da parede abdominal de ratos. Métodos: Foram utilizados 40 ratos adultos, submetidos à laparotomia mediana e distribuídos, aleatoriamente, em um grupo controle (C), constituído de 20 animais que receberam solução de NaCl a 0,9 %; e um grupo tratado (T), constituído de 20 animais que receberam o tenoxicam. Os animais de cada grupo foram divididos, conforme a data de sacrifício, em subgrupos de 10 animais, denomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The absence of dehiscence, fistulas or infections in all animals studied demonstrates that copaiba oil did not interfere in the process of healing of abdominal wall with enough intensity to cause early clinical changes as occurred in studies using tenoxicam 13 and meloxican 18 . Macroscopic results were similar to those found by Pundek et al 19 studying polypropylene/ polyglecaprone meshes.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The absence of dehiscence, fistulas or infections in all animals studied demonstrates that copaiba oil did not interfere in the process of healing of abdominal wall with enough intensity to cause early clinical changes as occurred in studies using tenoxicam 13 and meloxican 18 . Macroscopic results were similar to those found by Pundek et al 19 studying polypropylene/ polyglecaprone meshes.…”
Section: Discussionmentioning
confidence: 71%
“…Some anti-inflammatory drugs have already been tested in the healing of rats' abdominal walls, and the results remain controversial, depending on the drug group studied 12,13,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breaking strength assessment, despite exposing the scar to extremely adverse situations that are hardly encountered after operation, has been frequently used to determine surgical wound tissue cohesion at different healing stages 13,14 . In this study, no significant statistical difference in this variable was observed between groups at all time points.…”
Section: Discussionmentioning
confidence: 99%
“…The rats receive the standard diet with water ad libitum [10][11][12] . All the rats passed by the same operatory procedure.…”
Section: Methodsmentioning
confidence: 99%